#TITLE_ALTERNATIVE# - ROBIANTO (NIM : 21714001), AGUNG
Background: Physical fitness is an important component to get the best performance in sports, where the maximum oxygen uptake or VO2max becomes the gold standard to assessing physical fitness level. There are several types of test to measuring VO2max, that are laboratory test method using cardio pulmonary exercising test (CPET) and field test method using 2400 meter cooper run, bleep test, 15 minutes balke run, and 1600 meter walking rockport. Field test methods have been tested separately, but no studies have compared 2400 meter cooper run, bleep test, 15 minutes balke run, and 1600 meter walking rockport with laboratory test simultaneously on same population. Objctive: The aim of this study is to know the differences between laboratory test method using CPET with field test method using 2400 meter cooper run, bleep, 15 minutes balke run, and 1600 meter walking rockport. in VO2max measurement. Methodes: Subjects are 14 healthy men aged (20 ± 1,24) which have high physical activity level. Subjects conducted VO2max measurement test with laboratory test method using CPET and field test using 2400 meter cooper run, bleep, 15 minutes balke run, and 1600 meter walking rockport. Interval between each tests at least two days. Each test carried out measurements of VO2max, blood lactic acid level, maximum heart rate, calories expenditure, and rating of perceived exertion (RPE). Results: VO2max 15 minute balke run (44,88 ± 3,90), 2400 meters cooper run (46,20 ± 5,51), and bleep test (42,23 ± 6,25) did not have significant difference with laboratory test methode (44.66 ± 5.51), but 1600 meter walking rockport (54.36 ± 4.94) had a very significant differences (p <0.01). Maximum heart rate, blood lactic acid level, and RPE scores 2400 meter cooper run, 15 minutes balke run, and bleep test had no significant differences with laboratory test, but 1600 meter walking rockport was significantly different ( p <0.01) with a maximum heart rate (156.4 ± 10.1), blood lactic acid (4.05 ± 1.16) and RPE (4.14 ± 1.35). Calories expenditure during bleep test (141.5 ± 30.4) did not have a significant difference with laboratory test method (143.4 ± 21.3), while 2400 meter cooper run (201.6 ± 35), 15 minute balke run (259.4 ± 22.5), and 1600 meter walking rockport (165.1 ± 30.5) had a very significant differences (p <0.01). Conclusions: VO2max, maximum heart rate, blood lactic acid level, and RPE 2400 meters cooper run, bleep test, and 15 minute balke run have different result from laboratory test method using CPET but not significant. Whereas for VO2max, maximum heart rate, blood lactic acid levels, RPE, and calories expenditure 1600 meters walking rockport have significant differences with laboratory test method using CPET.